PENETAPAN HUKUM BAGI PELAKU DOSA BESAR, IMAN DAN KUFUR DALAM ALIRAN TEOLOGI - Amin, St. Jamilah (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This Article discusses how the legal determination commit major sins in the study of Islamic theology, is still said to be a believer or an infidel. The three principal problems is a major issue in this article. Even very surprisingly, the issue first appeared and debate is not a matter of theology, but political problems at the start with the death of the caliph Utsman ibn Affan to the three who were later replaced by the Caliph Ali ibn Abi Talib became Caliph to four. In the reign of Ali ibn Abi Talib these political upheavals began to appear. At the start the challenge and rebellion of the companions of the Prophet himself that Talha and Zubair with the Prophets wife, Aisha ra., Who refused Ali as caliph, Ali ibn abi Talib but can cripple the pemberontaka. Then the uprising Muawiya ibn abi Sufyan ended with the Siffin war , then do tahkim (arbitration) that led to the outbreak of Muslims into three groups at the time , namely Ali ibn abi Talib group, Muawiyah groups and groups Khawarij. Of events tahkim (arbitration) then this is a debate about the commit major sins, faith and kufr.